Electrochemical etching-chemical deposition of metal material super-hydrophobic surface and construction method thereof

CN122918548APending Publication Date: 2026-10-16ANGANG STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610989653.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]为解决现有超疏水表面存在易被破环失去超疏水性能的问题,本发明提供了一种电化学刻蚀-化学沉积金属材料超疏水表面及其构筑方法,该技术方案通过电化学刻蚀-化学沉积法制备具有超疏水表面的金属材料,所述表面为三层结构,包括电化学刻蚀层、化学沉积层和低表面能修饰层,其中电化学刻蚀层为由电化学刻蚀所产生的多级粗糙结构,化学沉积层为由化学沉积所产生的异种金属层,低表面能修饰层为低表面能有机物单分子层,该方法可以赋予普通金属材料以超疏水特性,相比于单一化学沉积钢超疏水表面,电化学刻蚀-化学沉积法金属材料超疏水表面的耐蚀性能得到进一步提升

Benefits of technology

本发明公开的技术方案通过电化学刻蚀-化学沉积法制备具有超疏水表面的金属材料,所述表面为三层结构,包括电化学刻蚀层、化学沉积层和低表面能修饰层,其中电化学刻蚀层为由电化学刻蚀所产生的多级粗糙结构,化学沉积层为由化学沉积所产生的异种金属层,低表面能修饰层为低表面能有机物单分子层,该方法可以赋予普通金属材料以超疏水特性,相比于单一化学沉积金属材料超疏水表面,电化学刻蚀-化学沉积法金属材料超疏水表面的耐蚀性能进一步提升,即在3.5wt%氯化钠溶液中阻抗弧半径为单一化学沉积法制备的超疏水表面的两倍以上,由于采用电化学刻蚀方法使得刻蚀时间大幅缩短,超疏水表面的制备效率大幅提升,且可对各类金属工件进行无应力刻蚀加工,不受材料硬度、韧性限制,此外刻蚀液不含强酸,操作安全。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application belongs to the technical field of chemical plating and material surface modification, and particularly discloses an electrochemical etching-chemical deposition metal material super-hydrophobic surface and a construction method thereof. The super-hydrophobic surface is composed of an electrochemical etching layer, a chemical deposition layer and a low-surface-energy modification layer. The substrate of the super-hydrophobic surface is selected from at least one metal material in steel, aluminum, copper and alloy. The multi-stage rough structure is composed of micro-nano rough structures generated after electrochemical etching. The heterogeneous metal layer is a metal after the substrate element. The low-surface-energy organic monolayer is a stearic acid, myristic acid and palmitic acid complex. The electrochemical etching-chemical deposition metal material super-hydrophobic surface is prepared by electrochemical etching, chemical deposition and low-surface-energy modification. The electrochemical etching method greatly shortens the etching time, greatly improves the preparation efficiency of the super-hydrophobic surface, and can be used for stress-free etching processing of various metal workpieces without being limited by material hardness and toughness. In addition, the etching solution does not contain strong acid and is safe to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical plating and material surface modification technology, specifically relating to an electrochemical etching-chemical deposition of a superhydrophobic surface of a metallic material and its construction method. Background Technology

[0002] Metal materials are widely used in the construction of ships, offshore platforms, bridges, high-voltage transmission lines and other industries. Traditional metal materials may encounter problems such as water condensation and icing and surface corrosion when exposed to humid environments during service. In particular, steel structures serving in extremely cold regions are prone to icing on their surfaces due to the characteristics of low temperature and high humidity service environments, which threaten service safety. At the same time, water and ice can also cause corrosion to metal materials.

[0003] In recent years, superhydrophobic materials have attracted widespread attention due to their unique superhydrophobic properties. Surfaces with a static contact angle with water greater than 150° are generally defined as superhydrophobic surfaces. They have application value in many aspects such as self-cleaning, anti-fouling, anti-corrosion, and anti-icing. Micro-nano layered structure and low surface energy are prerequisites for achieving superhydrophobic properties.

[0004] Currently, superhydrophobic modification of metal surfaces is generally achieved by altering their surface roughness or by modifying them with low surface energy materials. Methods for superhydrophobic surface modification mainly include deposition, sol-gel, hydrothermal synthesis, etching, template methods, and laser etching. Typically, a micro / nano structure is first prepared, and then a superhydrophobic surface is obtained through modification with low surface energy materials. Among these methods, vapor deposition and laser etching require more sophisticated equipment, are expensive, and have low production efficiency, making them unsuitable for large-scale production. Hydrothermal synthesis involves reactions in a sealed autoclave, resulting in high energy consumption. Template methods use soft or hard mold replication technology, which is unsuitable for products with complex shapes and has certain limitations. Etching methods use acidic or alkaline etching solutions for surface etching, resulting in lower production costs and simpler processes and equipment, but can lead to material loss. Chemical deposition can deposit other metallic elements on the surface of steel materials, serving to protect the base metal.

[0005] Currently, superhydrophobic surfaces constructed through chemical deposition modification of metallic materials suffer from the problem of easy surface damage leading to the loss of superhydrophobic properties, resulting in only a limited improvement in corrosion resistance compared to the metallic substrate. Developing an electrochemical etching-chemical deposition method for constructing superhydrophobic metallic surfaces can integrate the advantages of both methods, further enhancing the corrosion resistance of superhydrophobic surfaces. Summary of the Invention

[0006] To address the problem that existing superhydrophobic surfaces are easily damaged and lose their superhydrophobic properties, this invention provides an electrochemical etching-chemical deposition (ECD) superhydrophobic surface for metallic materials and its construction method. This technical solution prepares a metallic material with a superhydrophobic surface using an electrochemical etching-chemical deposition method. The surface has a three-layer structure, including an electrochemically etched layer, a chemically deposited layer, and a low surface energy modification layer. The electrochemically etched layer is a multi-level rough structure produced by electrochemical etching; the chemically deposited layer is a dissimilar metal layer produced by chemical deposition; and the low surface energy modification layer is a low surface energy organic monolayer. This method can endow ordinary metallic materials with superhydrophobic properties. Compared to a single chemically deposited steel superhydrophobic surface, the corrosion resistance of the electrochemical etching-chemical deposition method's superhydrophobic surface is further improved.

[0007] According to one aspect of the present invention, an electrochemical etching-chemical deposition metal material superhydrophobic surface is provided, the superhydrophobic surface being composed of an electrochemical etching layer, a chemical deposition layer and a low surface energy modification layer, wherein the electrochemical etching layer is a multi-level rough structure produced by electrochemical etching, the chemical deposition layer is a dissimilar metal layer produced by chemical deposition, and the low surface energy modification layer is a low surface energy organic monolayer. The substrate of the superhydrophobic surface is selected from at least one metallic material selected from steel, aluminum, copper, and alloys; The multi-level rough structure is composed of micro- and nano-scale rough structures generated after electrochemical etching, and has the function of increasing surface roughness. The dissimilar metal layer is a metal whose activity sequence is after that of the base element, and has the function of further increasing the surface roughness and protecting the base metal. The low surface energy organic monolayer is a complex of stearic acid, myristic acid, and palmitic acid, which has the function of increasing the superhydrophobic properties of the surface. The superhydrophobic surface of the electrochemically etched-chemically deposited metallic material is prepared by electrochemical etching, chemical deposition, and low surface energy modification.

[0008] Based on the above technical solution, the thickness of the multi-level roughness structure is 10~50μm; The thickness of the dissimilar metal layer is 1~50μm, and it is selected from at least one of zinc, nickel, copper, and silver; The thickness of the low surface energy organic monolayer is 2-5 nm; The water contact angle of the superhydrophobic surface is greater than 150°; The layers of the superhydrophobic surface are connected by molecular / atomic forces. The electrochemical etched layer is directly connected to the metal substrate, the chemically deposited layer is bonded to the chemically etched layer through interatomic forces, and the low surface energy modification layer is bonded to the chemically deposited layer through coordination bonds.

[0009] According to another aspect of the present invention, a method for constructing a superhydrophobic surface of a metallic material by electrochemical etching-chemical deposition is provided, comprising the following steps: metal surface pretreatment-electrochemical etching-chemical deposition-low surface energy modification; Step 1, metal surface pretreatment; Step 2, electrochemical etching: Using the pretreated sample as the anode and graphite as the counter electrode, the sample is placed in an etching solution for electrochemical etching and then cleaned to obtain the electrochemically etched sample. Step 3, chemical deposition; Step 4, low surface energy modification.

[0010] Based on the above technical solution, the metal surface pretreatment in step 1 is specifically as follows: sand the substrate with water sandpaper to 240~1200#, remove oil, degrease, and clean with deionized water to obtain the steel sample after surface pretreatment.

[0011] Based on the above technical solution, the substrate is one of steel, aluminum, copper, and alloys, preferably at least one of low-alloy steel, steel-cored aluminum stranded wire, and copper alloy. Based on the above technical solution, the etching solution in step 2, the electrochemical etching process, is a solution composed of inorganic salts and water. The inorganic salts are selected from at least one of sodium bicarbonate and sodium bisulfite. The concentration of the inorganic salts in the etching solution is 5-25 wt%, with the remainder being water, preferably a 5-25 wt% sodium bicarbonate solution with the remainder being water. The etching time is 30-300 s.

[0012] Based on the above technical solution, the chemical deposition in step 3 specifically involves: placing the electrochemically etched sample in a deposition solution for chemical deposition, cleaning it, and obtaining the chemically deposited sample.

[0013] Based on the above technical solution, the deposition solution is composed of a metal orthosalt with a metal activity sequence following that of the matrix element and water; The metal salt is selected from at least one of zinc chloride, copper chloride, copper sulfate, nickel sulfate, and nickel nitrate, with a concentration of 0.01~0.1 mol / L; The chemical deposition time is 0.5~10 min.

[0014] Based on the above technical solution, the low surface energy modification in step 4 is specifically as follows: the chemically deposited sample is placed in the modification solution for low surface energy modification for 30~120 min, and then cleaned and dried at 20~80℃ for 0.5~3 h to obtain a superhydrophobic surface.

[0015] Based on the above technical solution, the modification liquid is composed of organic low surface energy substances and organic solvents; The organic low surface energy substance is selected from at least one of stearic acid, myristic acid, and palmitic acid; The organic solvent is selected from at least one of ethanol, n-propanol, isopropanol, and acetone; The modifying solution is preferably at least one of the following: a stearic acid ethanol solution with a concentration of 0.01~0.1 mol / L, a mixed solution of isopropanol and acetone containing myristic acid, a palmitic acid n-propanol solution, and a stearic acid isopropanol solution, wherein the volume ratio of isopropanol to acetone in the mixed solution of isopropanol and acetone containing myristic acid is 1:1~3.

[0016] Beneficial effects The technical solution disclosed in this invention prepares metal materials with superhydrophobic surfaces using an electrochemical etching-chemical deposition method. The surface has a three-layer structure, including an electrochemically etched layer, a chemically deposited layer, and a low surface energy modification layer. The electrochemically etched layer is a multi-level rough structure produced by electrochemical etching; the chemically deposited layer is a dissimilar metal layer produced by chemical deposition; and the low surface energy modification layer is a low surface energy organic monolayer. This method can endow ordinary metal materials with superhydrophobic properties. Compared to superhydrophobic surfaces prepared by single chemical deposition, the corrosion resistance of superhydrophobic surfaces prepared by the electrochemical etching-chemical deposition method is further improved. Specifically, the impedance arc radius in a 3.5 wt% sodium chloride solution is more than twice that of superhydrophobic surfaces prepared by single chemical deposition. Because the electrochemical etching method significantly shortens the etching time, the preparation efficiency of superhydrophobic surfaces is greatly improved. Furthermore, it allows for stress-free etching of various metal workpieces, unaffected by material hardness or toughness limitations. In addition, the etching solution does not contain strong acids, ensuring safe operation. Attached Figure Description

[0017] Figure 1 A schematic diagram of the superhydrophobic surface structure of a metallic material using the electrochemical etching-chemical deposition method; Figure 2 The AC impedance spectra of the superhydrophobic surface of the steel-cored aluminum stranded wire JL / G1A-120 / 20 in Example 1 and Comparative Example 1 are shown. Figure 3 The AC impedance spectra of the superhydrophobic surface of FH36 ship plate steel in Example 2 and Comparative Example 2 are shown. Figure 4 The AC impedance spectra of the superhydrophobic surface of copper alloy HAl77-2 in Example 3 and Comparative Example 3 are shown. Detailed Implementation

[0018] To make the objectives and technical solutions of this invention clearer, the following embodiments are provided for further explanation. However, the scope of protection of this invention is not limited to these embodiments; the embodiments are merely for illustrative purposes. Those skilled in the art should understand that any changes or equivalent substitutions that do not depart from the concept of this invention are included within the scope of protection of this invention.

[0019] Unless otherwise specified, all reagents and raw materials used in this invention are obtained through purchase.

[0020] Example 1 The surface of steel-cored aluminum stranded wire JL / G1A-120 / 20 was polished to 1200# with water sandpaper, and then degreased, degreased, and cleaned with deionized water to obtain a pretreated sample. Electrochemical etching was performed on the pretreated sample using a 25wt% sodium bicarbonate aqueous solution as the etching solution, with the sample as the anode and graphite as the counter electrode. The etching time was 30s, and the sample was cleaned with deionized water after etching to obtain an electrochemically etched sample. Chemical deposition was then performed on the etched sample using a 0.05mol / L zinc chloride solution as the chemical deposition solution for 5min. After deposition, the sample was cleaned sequentially with deionized water and anhydrous ethanol. A chemically deposited sample (with a zinc chemically deposited layer) was obtained. The surface of the chemically deposited sample was modified with a 0.05 mol / L stearic acid-ethanol solution for 120 min, resulting in a modified sample (with a low surface energy modification layer of stearic acid complex). The modified sample was then cleaned with anhydrous ethanol and dried at 20°C for 10 min to obtain a superhydrophobic surface (water contact angle of 160.5°) for the electrochemical etching-chemical deposition method for steel-cored aluminum stranded wire JL / G1A-120 / 20. A schematic diagram of the structure of the JL / G1A-120 / 20 superhydrophobic surface is shown below. Figure 1 .

[0021] The superhydrophobic surface of the electrochemically etched-chemically deposited steel-cored aluminum stranded wire JL / G1A-120 / 20 was placed in a 3.5wt% sodium chloride solution to test its corrosion resistance. The test results are shown in [Figure number missing]. Figure 2 It can be seen that in a 3.5wt% sodium chloride solution, its impedance arc radius is more than twice that of the superhydrophobic surface of the steel-cored aluminum stranded wire JL / G1A-120 / 20 made by chemical deposition of steel plate A plate.

[0022] Example 2 The surface of FH36 ship plate steel was sanded to 1000# with wet sandpaper, and then degreased, degreased, and cleaned with deionized water to obtain a pretreated sample. Electrochemical etching was performed on the pretreated sample using a 5wt% sodium bisulfite aqueous solution as the etching solution, with the sample as the anode and graphite as the counter electrode, for a etching time of 300 seconds. After etching, the sample was cleaned with deionized water to obtain the electrochemically etched sample. A 0.1 mol / L copper chloride solution was used as the chemical deposition solution to perform chemical deposition on the etched sample for 0.5 min. After deposition, the sample was cleaned sequentially with deionized water and anhydrous ethanol to obtain the chemically deposited sample (the chemically deposited layer was copper). A 0.01 mol / L myristic acid isopropanol-acetone solution (isopropanol to acetone volume ratio 1:1) was used to modify the surface of the chemically deposited sample for 30 min to obtain the modified sample (the low surface energy modification layer was a myristic acid complex). The modified sample was cleaned with ethanol and dried at 50℃ for 5 min to obtain a superhydrophobic surface (water contact angle of 162.1°) of ship plate steel FH36 obtained by electrochemical etching-chemical deposition. A schematic diagram of the superhydrophobic surface structure is shown below. Figure 1 .

[0023] The superhydrophobic surface of the FH36 ship plate steel prepared by electrochemical etching-chemical deposition was placed in a 3.5wt% sodium chloride solution to test its corrosion resistance. The test results are shown in [Figure number missing]. Figure 3 It can be seen that in a 3.5wt% sodium chloride solution, its impedance arc radius is more than twice that of the superhydrophobic surface of FH36 steel plate by chemical deposition.

[0024] Example 3 The surface of the copper alloy HAl77-2 was polished to 600# with water sandpaper, and then degreased, cleaned with deionized water to obtain a pretreated sample. Electrochemical etching was performed on the pretreated sample using a 10wt% sodium bicarbonate aqueous solution as the etching solution, with the sample as the anode and graphite as the counter electrode. The etching time was 200s, and the sample was cleaned with deionized water after etching to obtain an electrochemically etched sample. Chemical deposition was then performed on the chemically etched sample using a 0.01mol / L silver nitrate solution as the chemical deposition solution for 10min. The sample was sequentially cleaned with deionized water and anhydrous ethanol to obtain a chemically deposited sample (the chemically deposited layer was silver). The surface of the chemically deposited sample was then modified with a 0.1 mol / L palmitic acid-propanol solution for 60 min to obtain a modified sample (the low surface energy modification layer was a palmitic acid complex). The modified sample was then cleaned with ethanol and dried at 80 °C for 1 min to obtain a copper alloy HAl77-2 etching-deposition coupled superhydrophobic surface (water contact angle of 161.7°). A schematic diagram of the structure of the steel superhydrophobic surface is shown below. Figure 1 .

[0025] The superhydrophobic surface of the copper alloy HAl77-2 obtained by electrochemical etching-chemical deposition was placed in a 3.5 wt% sodium chloride solution to test its corrosion resistance. The test results are shown in [Figure number missing]. Figure 4 It can be seen that in a 3.5wt% sodium chloride solution, its impedance arc radius is more than twice that of the superhydrophobic surface of copper alloy HAl77-2 by chemical deposition.

[0026] Comparative Example 1 Preparation method of superhydrophobic steel surface of JL / G1A-120 / 20 aluminum steel-cored stranded wire by chemical deposition: The surface of JL / G1A-120 / 20 aluminum steel-cored stranded wire was sanded with water sandpaper to 1200#, and then degreased, degreased, and cleaned with deionized water; 0.05 mol / L zinc chloride solution was used as the chemical deposition solution to chemically deposit the pretreated sample for 5 min, followed by cleaning with deionized water and anhydrous ethanol; 0.05 mol / L stearic acid ethanol solution was used to modify the surface of the chemically deposited sample for 120 min; the modified sample was cleaned with anhydrous ethanol and dried at 20℃ for 10 min to obtain the superhydrophobic steel surface of JL / G1A-120 / 20 aluminum steel-cored stranded wire by chemical deposition (water contact angle of 158.9°). Its corrosion resistance is shown in the figure. Figure 2 (3.5wt% sodium chloride solution).

[0027] Comparative Example 2 Preparation method of superhydrophobic surface of FH36 ship plate steel by chemical deposition: The surface of FH36 ship plate steel was sanded with water sandpaper to 1000#, and then degreased, degreased, and cleaned with deionized water. A 0.1 mol / L copper chloride solution was used as the chemical deposition solution to chemically deposit the pretreated steel sample for 0.5 min. After deposition, the sample was cleaned sequentially with deionized water and anhydrous ethanol. The surface of the chemically deposited sample was modified with a 0.01 mol / L myristic acid isopropanol-acetone solution for 30 min. The modified sample was cleaned with ethanol and dried at 50℃ for 5 min to obtain the superhydrophobic surface of FH36 ship plate steel by chemical deposition (water contact angle of 162.0°). Its corrosion resistance is shown in [the table below]. Figure 3 (3.5wt% sodium chloride solution).

[0028] Comparative Example 3 Preparation method of superhydrophobic steel surface by chemical deposition of copper alloy HAl77-2: The surface of marine engineering steel VL4-4 was sanded with water sandpaper to 600#, and then degreased, degreased, and cleaned with deionized water. A 0.01 mol / L nickel sulfate solution was used as the chemical deposition solution to chemically deposit nickel onto the pretreated steel sample for 10 min. After deposition, the sample was cleaned sequentially with deionized water and anhydrous ethanol. The chemically deposited steel surface was modified with a 0.1 mol / L palmitic acid-propanol solution for 60 min. The modified steel sample was then cleaned with ethanol and dried at 80℃ for 1 min to obtain a superhydrophobic surface of marine engineering steel VL4-4 obtained by chemical deposition (water contact angle of 161.2°). Its corrosion resistance is shown in [the table below]. Figure 4 (3.5wt% sodium chloride solution).

[0029] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A superhydrophobic surface for an electrochemically etched-chemically deposited metallic material, characterized in that, The superhydrophobic surface is composed of an electrochemical etching layer, a chemical deposition layer and a low surface energy modification layer. The electrochemical etching layer is a multi-level rough structure produced by electrochemical etching, the chemical deposition layer is a dissimilar metal layer produced by chemical deposition, and the low surface energy modification layer is a low surface energy organic monolayer. The substrate of the superhydrophobic surface is selected from at least one metallic material selected from steel, aluminum, copper, and alloys; The multi-level roughness structure is composed of micro- and nano-scale roughness structures generated after electrochemical etching. The dissimilar metal layer is a metal whose activity sequence is after that of the matrix element; The low surface energy organic monolayer is a complex of stearic acid, myristic acid, and palmitic acid. The superhydrophobic surface of the electrochemically etched-chemically deposited metallic material is prepared by electrochemical etching, chemical deposition, and low surface energy modification.

2. The superhydrophobic surface of an electrochemically etched-chemically deposited metallic material according to claim 1, characterized in that, The thickness of the multi-level roughness structure is 10~50μm; The thickness of the dissimilar metal layer is 1~50μm, and it is selected from at least one of zinc, nickel, copper, and silver; The thickness of the low surface energy organic monolayer is 2-5 nm; The water contact angle of the superhydrophobic surface is greater than 150°.

3. A method for constructing a superhydrophobic surface of a metallic material using electrochemical etching-chemical deposition, characterized in that, The process includes the following steps: metal surface pretreatment - electrochemical etching - chemical deposition - low surface energy modification; Step 1, metal surface pretreatment; Step 2, electrochemical etching: Using the pretreated sample as the anode and graphite as the counter electrode, the sample is placed in an etching solution for electrochemical etching and then cleaned to obtain the electrochemically etched sample. Step 3, chemical deposition; Step 4, low surface energy modification.

4. The construction method according to claim 3, characterized in that, The metal surface pretreatment described in step 1 is as follows: the substrate is sanded with sandpaper to 240~1200#, degreased, cleaned with deionized water, and the steel sample after surface pretreatment is obtained. The substrate of the superhydrophobic surface is one of steel, aluminum, copper, and alloy, preferably at least one of low alloy steel, steel-cored aluminum stranded wire, and copper alloy.

5. The construction method according to claim 3, characterized in that, The etching solution in step 2 is a solution composed of inorganic salt and water, wherein the inorganic salt is selected from at least one of sodium bicarbonate and sodium bisulfite; The etching solution contains 5-25 wt% inorganic salts, with the remainder being water, preferably a 5-25 wt% sodium bicarbonate solution with the remainder being water; the etching time is 30-300 s.

6. The construction method according to claim 3, characterized in that, The chemical deposition in step 3 specifically involves placing the electrochemically etched sample in a deposition solution for chemical deposition, followed by cleaning to obtain the chemically deposited sample.

7. The construction method according to claim 6, characterized in that, The deposition solution consists of a metallic salt following the matrix elements and water; The metal salt is selected from at least one of zinc chloride, copper chloride, copper sulfate, nickel sulfate, and nickel nitrate, with a concentration of 0.01~0.1 mol / L; The chemical deposition time is 0.5~10 min.

8. The construction method according to claim 3, characterized in that, The low surface energy modification in step 4 specifically involves placing the chemically deposited sample in a modification solution for 30-120 minutes for low surface energy modification, followed by cleaning and drying at 20-80°C for 0.5-3 hours to obtain a superhydrophobic surface.

9. The construction method according to claim 8, characterized in that, The modification solution is composed of organic low surface energy substances and organic solvents; The organic low surface energy substance is selected from at least one of stearic acid, myristic acid, and palmitic acid; The organic solvent is selected from at least one of ethanol, n-propanol, isopropanol, and acetone; The modifying solution is preferably at least one of the following: a stearic acid ethanol solution with a concentration of 0.01~0.1 mol / L, a mixed solution of isopropanol and acetone containing myristic acid, a palmitic acid n-propanol solution, and a stearic acid isopropanol solution, wherein the volume ratio of isopropanol to acetone in the mixed solution of isopropanol and acetone containing myristic acid is 1:1~3.